Fenomena Politik Uang Pada Pemilu Indonesia : Tantangan Dalam Mewujudkan Demokrasi Pancasila - Febriadinata Febriadinata; Wahyu Nur Laili; muhammad afandi (Jurnal Bawaslu Provinsi Kepulauan Riau, 2025)
Democracy is a form of government in which sovereignty is absolutely placed in the hands of the people, either directly or indirectly through a representative system. Indonesia, as an independent and sovereign nation, adopts these democratic principles but adjusts them to align with the country's cultural values and national ideology. The form of democracy practiced in Indonesia is known as Pancasila Democracy.As a serious violation of the principles of free and fair elections, money politics is strictly prohibited under various legal regulations in Indonesia. The Election Law bans all forms of material gifts to voters by election participants or campaign teams. Article 280 paragraph (1) point (j) explicitly prohibits promising or giving rewards to voters, while Article 515 stipulates criminal sanctions in the form of imprisonment for up to 3 (three) years and a maximum fine of IDR 36 million for violators.Money politics refers to the practice of giving money, goods, or other material incentives by election participants or related parties to influence voters' choices. This phenomenon not only contradicts democratic principles but also violates the values of Pancasila, particularly the fourth and fifth principles. It can also be seen as a form of financial inequality in political contests. As a result, the people may become increasingly marginalized and lose their strategic role in determining the direction of future political policies.